Women, the crusades, the Templars and Hospitallers in medieval European society and culture - Nicholson, Helen J., 1960- author. Link
1 online resource.
Keywords: "Known worldwide among scholars of medieval Europe for her books on the Knights Hospitaller and the Knights Templar, the trial of the Templars in Britain and Ireland, and women and the crusades, Professor Helen J. Nicholson has drawn together in this volume a selection of her shorter publications, previously published in academic journals, scholarly collections, or online. Reflecting almost thirty years of published research, this collection includes articles focusing on women's depiction in contemporary writing on the crusades and their involvement with the military religious orders, the Templars' and Hospitallers' relations with the rulers of Latin Christendom and with their noble patrons, and their operations in Britain and Ireland. Women, the Crusades, the Templars and Hospitallers in Medieval European Society and Culture will interest scholars, students, and other researchers studying the military religious orders, the crusades, and women's lives in medieval Europe and the crusader states"--